Surgical Reconstruction of Perineal Laceration in a Crossbred Jersey Cow - Selvaraju, Mani; Ruthrakumar, Ravichandran; Sathriyan , Gunasekaran; Napolean, Rayappan Ezakial (The Indian Journal of Animal Reproduction, 2023)
A 6-year-old Jersey × Holstein Friesian cow was presented with history of vulval tear due to improper handling of dystocia by the owner. The foetal membranes were hanging from the vaginal canal through vulval tear. Clinical examination revealed all physiological parameters were within the normal range. Obstetrical examination revealed extensive tear from the caudal vagina up to vulva and the fetal membranes were hanging from both vulval passage and through tear in the vulva. The reconstructive surgery was performed under epidural anaesthesia. Post-operatively the animal was treated with Inj. Calcium borogluconate 450 ml i.v. besides Inj. Ceftriaxone at 20mg/kg i.v., Inj. Flunixin meglumine at 2.2mg/kg i.m., and Inj. Chlorpheniramine maleate at 0.5mg/kg i.m. for three days. The skin sutures were removed on 10th post operative day. The animal recovered uneventfully.
Keywords: Perineal laceration; Dystocia; Reconstructive surgery; Cow